Implementation of Knowledge Based Life Support Nursing in the Emergency Installation of Palaloi Hospital, Maros Regency - Nursinah, Andi; Achmad, Viyan Septiyana; Prihatini, Surya; Hadi, Irwan; Handani, Nur; Mesa, Nofita Dewi Kok (International Journal of Health Sciences, 2024)
Basic life support is a series of emergency measures designed to save the life of a person experiencing a life-threatening medical condition. Basic life support can be used in any situation, from a heart attack to an accident. Basic life support is the first effort made to maintain life when a sufferer experiences a threatening situation. Emergency events cannot be predicted and can happen anywhere and to anyone. Delays and errors in handling them can have very fatal effects and cannot be corrected in subsequent actions. The aim of this research is to look for similarities, advantages and disadvantages regarding the description of knowledge and implementation of basic life support for emergency nurses in the emergency department. This research method uses a correlational descriptive method. This research uses a sample with inclusion and exclusion criteria. Data analysis is based on percentages and described in a frequency distribution table. The results of the research show a relationship between knowledge and skills of nurses in carrying out basic life support measures in the emergency department at Palaloi Hospital, Maros Regency. The level of relationship between the two variables is that the strength of the relationship is at a medium relationship level. Apart from that, this positive relationship means an increase in knowledge followed by an increase in nurses' skills in carrying out basic life support actions.